2009 IEEE International Conference on Computer Design 2009
DOI: 10.1109/iccd.2009.5413132
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive online testing for efficient hard fault detection

Abstract: Abstract-With growing semiconductor integration, the reliability of individual transistors is expected to rapidly decline in future technology generations. In such a scenario, processors would need to be equipped with fault tolerance mechanisms to tolerate in-field silicon defects. Periodic online testing is a popular technique to detect such failures; however, it tends to impose a heavy testing penalty. In this paper, we propose an adaptive online testing framework to significantly reduce the testing overhead… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 26 publications
0
9
0
2
Order By: Relevance
“…4) Customizable: Unlike prior approaches, approximate circuits provide a common framework that can be customized to provide concurrent error masking for a broad range of failure mechanisms. For example, offline architectural techniques such as periodic testing [8]- [10], [31], lifetime-reliability tracking based on technology parameters [32], and error prediction techniques [20], [21], [24], [25] target only timing errors resulting from gradual slowdown of speed paths, e.g., due to aging mechanisms. On-chip temperature and voltage sensors to predict temperature surges and voltage droops [33] target timing errors due to fast-changing dynamic variability effects such as supply voltage and temperature variations.…”
Section: ) Overhead Versus Error Coverage Tradeoffs: Unlike Tradi-mentioning
confidence: 99%
“…4) Customizable: Unlike prior approaches, approximate circuits provide a common framework that can be customized to provide concurrent error masking for a broad range of failure mechanisms. For example, offline architectural techniques such as periodic testing [8]- [10], [31], lifetime-reliability tracking based on technology parameters [32], and error prediction techniques [20], [21], [24], [25] target only timing errors resulting from gradual slowdown of speed paths, e.g., due to aging mechanisms. On-chip temperature and voltage sensors to predict temperature surges and voltage droops [33] target timing errors due to fast-changing dynamic variability effects such as supply voltage and temperature variations.…”
Section: ) Overhead Versus Error Coverage Tradeoffs: Unlike Tradi-mentioning
confidence: 99%
“…In contrast, our hybrid solution takes advantage of the low cost of software testing, but improves its coverage through the addition of extra observation points. Gupta, et al [7] suggested tuning the execution of functional tests to the health of the silicon elements within the processor. They estimate hardware health through in-situ oxide breakdown and NBTI sensors spread throughout the silicon, thus increasing chip area by 2.6%.…”
Section: Related Workmentioning
confidence: 99%
“…One way to do it is to retry the same computation multiple times, and after a certain number of errors in a given interval of time, declare the component as permanently faulty [2].…”
Section: Introductionmentioning
confidence: 99%